Application of Fluorescent-Antibody Procedures to the Study of Pathogenic Dematiaceous Fungi II. Serological Relationships of the Genus Fonsecaea - Gordon, Morris A. (1965)
Gordon, Morris A. (New York State Department of Health, Albany), and Yousef Al-Doory. Application of fluorescent-antibody procedures to the study of pathogenic dematiaceous fungi. II. Serological relationships of the genus Fonsecaea. J. Bacteriol. 89:551–556. 1965.—The staining spectra of fluorescein-labeled antiglobulins to Fonsecaea compactum, F. dermatitidis, and F. pedrosoi were determined with respect to 71 strains of morphologically related and 21 miscellaneous molds (including so-called “black yeasts”). All three conjugates showed considerable reaction with saprophytic Cladosporium spp. F. dermatitidis appeared to be most closely related serologically to the genus Cladosporium; F. compactum conjugate was fairly specific; and the few non-specific reactions of diluted F. pedrosoi reagent were almost unexceptionally with species of Fonsecaea and Cladosporium. Most strains of F. pedrosoi were unstained by F. compactum conjugate, and there was very little relationship shown between either of these species and Phialophora verrucosa. Conjugates of two strains of P. verrucosa failed to react with any of the three species of Fonsecaea. The possible significance of these results for classification of the “black yeasts” and other dematiaceous molds is discussed.